Antimicrobial Properties of Shrevestakadi Yoni Dhoopan for Management of Abnormal Vaginal Discharge (AYUSHDHARA, 2024)
Ayurveda, an ancient system of medicine adopts a holistic approach, focusing on both curing diseases and enhancing the overall well-being of individuals. It emphasizes the importance of maintaining a balance between the individual (body, mind, soul, spirit) and the environment. It includes a range of pharmaceutical preparations and therapeutic techniques. However, in the contemporary era, only a limited number of these procedures are actively employed, leading to the loss of significance and recognition for numerous valuable formulations and techniques, Dhoopan karma being one of them. "Dhoopana" is a procedure involving the use of herbal, herbo-mineral, or animal-origin substances for fumigation. Dhoopan has been actively used as a preventive measure during pre and post-operative care and as a therapeutic procedure due to its antimicrobial, analgesic, anti-inflammatory properties. Yoni Dhoopan is effectively utilized in addressing diverse Yonivyapad conditions. Medicinal properties of Dhoopan drugs includes Kashaya and Tikta in Rasa, Katu in Vipaka, and Laghu and Ruksha in Guna, rendering them to be a potent Kledashoshaka, Shodhaka (detoxifier), and ropaka (wound-healer). Furthermore, it exhibits Yoni doshhara, Kledashoshaka, and Jantughana (anti-microbial) properties.